A Tear of the Right Ventricular Outflow Tract during Pulmonary Valvuloplasty Treated by Transcatheter Sapien Valve Implantation. (4th July 2012) - Kefer, Joelle; Gewillig, Marc; Sluysmans, Thierry
Abstract: A 74‐year‐old woman was treated by balloon pulmonary valvuloplasty for a symptomatic restenosis 30 years after surgical commissurotomy. The valve dilatation was complicated by a rupture of the right ventricular outflow tract, treated in emergency by a covered stent implantation. The hemodynamic situation was improved, but the free pulmonary regurgitation was leading to a symptomatic right ventricular enlargement. Because surgery was not a good option in this patient at high risk, restoration of pulmonary valve competence was performed by a transcatheter Sapien valve implantation. Transcatheter approach allowed to treat the severe complication of pulmonary valvuloplasty without risk associated with an emergent and redo surgery in a high‐risk patient.